Innovation, economic development, and intellectual property in India and China : comparing six economic sectors - Liu, Kung-Chung, 1961-; Racherla, Uday S., 1954- (ARCIALA series on intellectual assets and law in Asia., 2019)
This open access book analyses intellectual property codification and innovation governance in the development of six key industries in India and China. These industries are reflective of the innovation and economic development of the two economies, or of vital importance to them: the IT Industry; the film industry; the pharmaceutical industry; plant varieties and food security; the automobile industry; and peer production and the sharing economy. The analysis extends beyond the domain of IP law, and includes economics and policy analysis. The overarching concern that cuts through all chapters is an inquiry into why certain industries have developed in one country and not in the other, including: the role that state innovation policy and/or IP policy played in such development; the nature of the state innovation policy/IP policy; and whether such policy has been causal, facilitating, crippling, co-relational, or simply irrelevant. The book asks what India and China can learn from each other, and whether there is any possibility of synergy. The book provides a real-life understanding of how IP laws interact with innovation and economic development in the six selected economic sectors in China and India. The reader can also draw lessons from the success or failure of these sectors.